How do I learn Mandarin Chinese, at this age? Chinese character acquisition in Singaporean adults - Cheng, Jasmine (Nanyang Technological University, 2020)
This paper reports two experiments on the effects of visual complexity and radical presence in Chinese characters, as well as the relationship between radical awareness i.e. positional regularity of radicals and character acquisition. The participants in this study included undergraduates of Nanyang Technological University between ages 21 and 26 and all stimuli used were novel characters. Experiment 1 was a lexical decision task that investigated participants’ ability to identify a non-character from a pseudo-character based on the position of radicals. Drawing on the Dual-coding Theory, Experiment 2 was a novel character acquisition task that explored the acquisition of character meaning with a 2x2 factorial design based on visual complexity and radical presence. The Two-Way Repeated Measures ANOVA has shown a main significant effect in visual complexity, such that complex characters had a higher rate of acquisition. There was no main effect in radical presence and only a marginally significant interaction between the two variables. With the use of Pearson’s correlation coefficient, participants’ radical awareness was found to correlate strongly with character acquisition rates.